PENERAPAN MODEL PICTURE AND PICTURE MENGGUNAKAN MEDIA VIDEO ANIMASI UNTUK MENINGKATKAN KEMAMPUAN MENULIS TEKS DESKRIPSI SISWA KELAS II UPTD SD NEGERI PEUSANGAN - Maulana, Riska; Syahrin, Alfi; Agustisa, Mutia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low descriptive writing skills of second-grade students at UPTD SD Negeri 2 Peusangan due to the limited use of innovative learning models and instructional media in the learning process. This study aimed to improve students' descriptive writing skills through the implementation of the Picture and Picture learning model assisted by animated video media, to describe teacher and student activities during the learning process, and to identify teacher and student responses toward the implementation of the learning model. This research employed a qualitative approach using Classroom Action Research (CAR) conducted in two cycles. The research subjects were second-grade students of UPTD SD Negeri 2 Peusangan. Data were collected through observation, tests, interviews, and documentation and analyzed using qualitative and quantitative descriptive techniques. The results showed that the implementation of the Picture and Picture learning model assisted by animated video media improved students' descriptive writing skills, increased teacher and student learning activities in each cycle, and generated positive responses from both teachers and students. These findings indicate that the implementation of the Picture and Picture learning model assisted by animated video media is effective in improving descriptive writing skills among elementary school students. Keywords: Picture and Picture, animated video, descriptive writing skills